Elucidating effects of Eu and P on solidification and precipitation of Al-7Si-0.3Mg based alloys refined by Ta and TiB2 - Ivo Spáčil; Dominik Gehringer; David Holec; Mihaela Albu; Jiehua LI (Journal of alloys and compounds, 2024)
Effects of Eu (up to 500 ppm) and P (up to 40 ppm) on solidification and precipitation of Al-7Si-0.3Mg based alloys refined by solute Ta (0.12 wt%) and stochiometric Al-2.2Ti-1B grain refiner were investigated using optical microscopy, differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) as well as density functional theory (DFT) calculations. It was found that (i) solute Ta can refine α-Al grains and is unaffected by the addition of Eu and/or P. (ii) 200 ppm Eu is eligible enough to modify eutectic Si although its modification effect can be enhanced with higher Eu additions (up to 500 ppm). (iii) A high P concentration (40 ppm) counteracts the modification effect in the alloy modified with 200 ppm Eu and therefore unmodified structure is obtained. (iv) Even with the addition of Eu and P, the activation energy of stable β-Mg 2Si is calculated to be very low (60–70 kJ/mol), indicating a short time for the precipitation of β-precipitates. Furthermore, one possible nucleation sequence in Al-Si-Mg based alloys modified with Eu or Sr has been proposed based on the lattice mismatch calculation and thermodynamic stability. Finally, DFT calculations suggest that Eu is energetically favourable for TPRE growth mechanism. The present investigation provides new insights into controlling solidification microstructure (mainly for the grain refinement of α-Al and eutectic grains) and precipitation microstructure (mainly for β-MgSi precipitate) of Al-7Si-0.3Mg based alloys via the addition of Ta and TiB 2 as a refiner of α-Al and the addition of Eu and P as a modifier of eutectic Si.
Publisher Copyright: extcopyright 2024 The Authors
Keywords: AlSiMg based alloys; DFT; DSC; Grain refinement; Heat treatment; Modification; TEM